Value of Platelet Indices in Evaluation of Varicocele Patients and Its Associated Abnormal Semen Parameters: A Cross Sectional Study - Mohamed Ahmed; Mohamed Kamel; AbdElaleem Elgendy (International Journal of Medical Arts, 2023)
Background: Varicocele is present in up to 19–41% of men with primary infertility and 80% of men with secondary infertility. Varicocele is associated with abnormal semen parameters. The role of platelet indices [PIs] in many vascular diseases, including varicocele, has been widely studied.Aim of the Study: The aim of this study was to evaluate the platelet indices in varicocele patients and its value in association with abnormal semen parameters.Patients and Methods: A cross sectional study was conducted on 122 male patients with varicocele, recruited from Dermatology, Venereology & Andrology Outpatient Clinics in Al-Azhar University Hospitals, Cairo, Egypt. The patients were classified into two groups [61 patients with varicocele associated with normal semen parameters and 61 patients with varicocele associated with abnormal semen parameters]. All patients were subjected to history taking, general and genital examination, complete blood count [CBC] and Scrotal Doppler Ultrasound. PIs were then compared between the two groups by their characteristics and grade of varicocele using appropriate statistical tests.Results: Of the studied platelet indices, the mean platelet volume [MPV] and plateletcrit [PCT] were significantly higher in varicocele group associated with abnormal semen parameters compared to varicocele group associated with normal semen parameters [9.5 ± 1.4 vs. to 7.9 ± 0.98; and 0.22 ± 0.05 vs. 0.18 ± 0.04]. In the varicocele group associated with abnormal semen parameters, the mean PCT and platelet distribution width [PDW] were significantly higher in the studied varicocele grades II and III compared to grade I. A significant moderate positive correlation was found between MPV and PCT and the number of sperms in the varicocele group associated with abnormal semen parameters.Conclusion: The study findings indicating that MPV and PCT were significantly higher in Varicocele patients with abnormal semen parameters than in normospermic varicocele patients.